A study of knowledge and skill among Nurses regarding basic neonatal resuscitation in selected districts of Chhattisgarh: Assessing Knowledge and Skill of Nurses in Neonatal Resuscitation (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Millions of newborns worldwide are not breathing at delivery every year, and the vast majorityof them need some kind of infant resuscitation. Safe and healthy babies can only be ensured if deliveryroom staff has a solid grasp of infant resuscitation techniques. Finding out how well-versed nurses arein neonatal resuscitation was the driving force for this research. To assess nurses' familiarity withneonatal resuscitation techniques, a descriptive cross-sectional research was conducted. Participantswere chosen using a census-style random selection process. The 86 nurses working in the maternityward of the non-governmental health institution in the Parsa District were interviewed using a semistructuredinterview schedule, and their skills were evaluated using an observational rating scale. 93 ofrespondents had insufficient knowledge (85 score) and 90.7 had insufficient ability (85 score) inNewborn Resuscitation, according to the study's results. There are statistically significant correlationsbetween the amount of time spent in the workforce (p=0.034), time spent working in a maternity ward(p=0.028), and completion of newborn resuscitation training (p=0.001), all of which contribute to a higherlevel of competence when it comes to resuscitating newborns. Findings showed a good connectionbetween respondents' knowledge score and ability score on the same question about infantresuscitation (p0.0018). In this Study discuss the knowledge and skill among Nurses regarding basicneonatal resuscitation in selected districts of Chhattisgarh.